Research on the reliable test range of four-point supported piezoelectric dynamometer. Issue 2 (13th January 2022) - Zhang, Jun; Ma, Yixuan; Ren, Zongjin; Bai, Tao; Hu, Peikai; Wang, Zunhao
Abstract : Purpose: The purpose of this paper is to improve the reliability of the force measurement system by determining the reliable test range of dynamometer. Design/methodology/approach: Based on the principle of leverage and moment balance, a general force distribution model is applicable in where the test point is located either inside or outside the support region of four three-component force links of dynamometer is established. After corroborating the correctness of the model through verification experiments, the boundary conditions that each three-component force link should satisfy are analyzed by considering the characteristic of the dynamometer components comprehensively. Furthermore, the reliable test range of dynamometer is determined, followed by a calibration experiment to verify its rationality. Findings: The relationships between the reliable test range and the tested force, the bolt pre-tightening force and the bearing capacity of quartz wafers are clarified. Further, the experimental calibration results show that when the test point is within the reliable test range, the three-directional output voltage of dynamometer has excellent linearity and repeatability. The nonlinearity and repeatability in X-, Y- and Z-directions are all less than 1.1%. Originality/value: A general mathematical model of force distribution of four three-component force links is constructed, which provides a theoretical basic for the mechanical analysis of multi-sensors' dynamometer. Comprehensively considering the performance of dynamometer components, the value of measured force and the pre-tightening force, the simultaneous equations of reliable test range are deduced, which limits the boundary of allowable test position of piezoelectric dynamometer.